PENGARUH HUBUNGAN POLITIK DAN KUALITAS AUDIT TERHADAP LIKUIDITAS SAHAM DI BURSA EFEK INDONESIA (BEI) TAHUN 2013-2018 - Yusuf Akhmadi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
Government intervention in a company can provide benefits for the company so that they will gain trust by increasing business trading in the stock market. In addition, audit quality also contributes to stock liquidity, because investors can judge the company's performance based on the results of the company's audit. This study aims to discuss the political relationship and audit quality of stock liquidity. The sampling method is based on a purposive sampling of 170 manufacturing institutions listed on the Indonesia Stock Exchange in the period 2013-2018, Utilizing SPSS version 15. The analytical tool used is the classic assumption test, T test and F. Test. The results showed that Political Connection directly had a significant positive effect on the Stock Liquidity of 34 Manufacturing Companies listed on the IDX in 2013-2018. Furthermore, Audit Quality directly had a significant negative effect on the Stock Liquidity of 34 Manufacturing Companies listed on the IDX in the year 2013-2018. Keywords:Political connections , Audit Quality , Liquidity Shares